Predictors of neonatal mortality referred to a tertiary care teaching institute: A descriptive study - Sachan, Ravi; Singh, Aaradhana; Kumar, Durgesh; Yadav, Rajesh; Singh, D K; Shukla, K M (Indian Journal of Child Health, 2016)
Objective: To assess the predictors of neonatal mortality transported to our institution from other hospitals. Methods: In this descriptive study, neonates who were delivered outside of the hospital premises and were referred to our tertiary care teaching institute were enrolled in the study and the following information were recorded - gestational ages in completed week, place of birth, stabilization of newborn before and during transportation, and clinical parameter on hospital arrival. Management of neonatal illness was performed as per the standard protocol. Predictors of neonatal mortality were assessed. Results: Out of 245 referred neonates included in the study, 45 expired. Number of babies delivered at home and conducted by unskilled birth attendant was 46 (18.8%) and at private hospitals was 82 (33.5%). Government ambulance facility for neonatal transport was used only in 80 (32.6%). Among the expired neonate, 73.3% of the babies were delivered by unskilled birth attendants (odds ratio [OR]: 16.60, 95% confidence interval [CI]: 4.57-60.19, p=0.0001). Neonatal mortality was significantly less when baby referred or admitted early, i.e.